The Electrical Properties of Single-walled Carbon Nanotubes. Issue 5 (January 2021) - Liu, Junzhi
Abstract: Carbon nanotubes are expected to be a new type of semiconductor material to replace the traditional silicon-based semiconductor material. The high carrier mobility, ideal subthreshold characteristics and ballistic transport characteristics of carbon nanotubes can effectively solve the short channel effect, performance and power consumption limits of silicon-based semiconductor devices. These excellent properties are due to the structure of carbon nanotubes. This paper focuses on the relationship between the structure of carbon nanomaterials and their electrical properties, and the advantages and prospects of using carbon nanotubes as semiconductor materials are also described.